Impact of the segregation energy spectrum on the enthalpy and entropy of segregation. (December 2021) - Scheiber, Daniel; Romaner, Lorenz
Graphical abstract: Abstract: Substantial disagreement exists for segregation energies between experimentally measured and first principles calculated values. To resolve this standing issue, we computed segregation of five different elements to the same grain boundaries as studied in an previous experimental investigation. We show that the multi-site nature of segregation leads to a strong artificial temperature dependence in the single site effective segregation energy. Taking this into account leads to a highly improved agreement between experiment and theory and clarifies the nature of experimentally determined segregation enthalpies and entropies.